Studi Hadis tentang Ilmu Pengetahuan - Nafis, Ahmad Jauhar; Asmi, Shabrina Tsabita; Zuhrin, Aida; Afriatus, Niroya (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2025)
Knowledge drives societal progress, including the development of moral values, ethics, and civilization. Islam places great importance on the pursuit of knowledge, as reflected in various sayings (hadith) of Prophet Muhammad SAW. Islam encourages its followers to seek knowledge and elevates those who possess it, both in religious and social life. This paper discusses several hadiths related to knowledge. Knowledge is a key means to draw closer to Allah and improve human life. This research employs a library research approach to analyze the messages contained in these hadiths, using primary sources such as authentic hadith books and secondary sources from various scholarly articles. The primary focus is to illustrate the strategic role of knowledge in Islamic teachings in building a progressive Muslim society. The study's findings highlight that these hadiths emphasize knowledge as a fundamental foundation for building quality individuals and communities. The hadiths on knowledge also inspire the younger generation to continuously learn and adapt to the changing times.